Copper grid lines and uses

By designing a copper grid structure and using small-particle copper powder to form dense contact on the surface of the solar cell, the problem of copper grid oxidation and corrosion was solved, achieving low resistivity and high-efficiency current collection, and reducing material costs.

CN121712149BActive Publication Date: 2026-11-03LONGI GREEN ENERGY TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411244287.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-05
Publication Date
2026-11-03
Estimated Expiration
2044-09-05

AI Technical Summary

Technical Problem

Silver is used in large quantities in solar cells but is scarce. Copper, as a substitute material, is prone to oxidation or corrosion, which leads to a decrease in conductivity, especially at the micro- and nano-scale, where it is difficult to achieve high conductivity.

Method used

A copper grid structure is designed, comprising a main grid part and an outer part. The copper powder particle size of the outer part is smaller than that of the main part. It is prepared by screen printing. The small and densely arranged copper powder particles in the outer part form a tight contact with the battery surface, reducing the contact resistivity.

Benefits of technology

This achieves high adhesion between the copper grid lines and the battery surface, reduces bulk resistivity and contact resistivity, improves current collection efficiency, and reduces material costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005031202320000071
    Figure BDA0005031202320000071
  • Figure BDA0005031202320000072
    Figure BDA0005031202320000072
  • Figure BDA0005031202320000131
    Figure BDA0005031202320000131
Patent Text Reader

Abstract

The application provides a copper grid line and use, the copper grid line includes a grid line main body part and a grid line peripheral part, the grid line peripheral part is located on both sides of the grid line main body part, wherein the width of any one side of the grid line peripheral part does not exceed 15%-50% of the width of the grid line main body part; the median value of the copper powder particle size of the grid line peripheral part is less than the median value of the copper powder particle size of the grid line main body part, because a dense structure can be formed in the grid line peripheral part, the contact area of the copper grid line and the battery surface is increased, the adhesion of the copper grid line is improved, water and oxygen are prevented from penetrating from the interface between the copper grid line and the bottom battery and oxidizing the copper powder of the grid line main body part, thereby reducing the volume resistivity of the grid line and the contact resistance between the grid line and the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of solar cell technology, and more particularly to a copper grid wire and its application. Background Technology

[0002] Silver is used in large quantities in solar cells. As a precious metal, silver has limited proven reserves, so finding a substitute for silver is of great strategic significance.

[0003] Among all metals, copper is the most promising alternative. Copper's conductivity is roughly equivalent to silver, but its price is only one-eightieth that of silver. Compared to silver, copper's biggest disadvantage is its high reactivity; it is easily oxidized or corroded, leading to a decrease in conductivity, especially at the micro- and nano-scale. Therefore, developing highly conductive copper grid lines is of great significance. Summary of the Invention

[0004] Based on the technical problems existing in the prior art, this application provides a copper grid wire and its application. The copper grid wire is prepared using copper paste, which can diffuse the copper paste onto the main grid wire, increase the contact area, and reduce the contact resistivity.

[0005] The specific technical solution of this application is as follows:

[0006] This application provides a copper grid line, comprising a grid line body portion and a grid line periphery portion, wherein the grid line periphery portion is located on both sides of the grid line body portion, and the width of the grid line periphery portion on either side does not exceed 15%-50% of the width of the grid line body portion; the median value of the copper powder particle size of the grid line periphery portion is smaller than the median value of the copper powder particle size of the grid line body portion.

[0007] Furthermore, the width of the main body of the copper grid line is 30-120 micrometers.

[0008] Furthermore, the width of the outer portion of the copper grid line is 10-60 micrometers, and / or the height of the outer portion of the copper grid line is 0.05-2.5 micrometers.

[0009] Furthermore, the height of the main body of the copper grid line is 10-25 micrometers.

[0010] Furthermore, the copper grid line comprises nanoscale spherical copper powder and micron-scale flake copper powder, wherein the median particle size of the spherical copper powder is 100-700 nm, the median diameter of the flake copper powder is 2-8 μm, and the median thickness of the flake copper powder is 100 nm-500 nm.

[0011] Furthermore, based on the mass percentage of the copper powder, the micron-sized flake copper powder accounts for 40-70%, and the nano-sized spherical copper powder accounts for 30-60%.

[0012] Furthermore, the copper grid line comprises nanoscale spherical copper powder and micron-scale sheet-like copper powder, and the outer portion of the grid line comprises only nanoscale spherical copper powder.

[0013] Furthermore, the copper grid lines are prepared by screen printing.

[0014] Furthermore, the copper grid line comprises nanoscale spherical copper powder and micron-scale flake copper powder, wherein the surface of the flake copper powder is adhered to the surface of the copper grid line in a substantially horizontal state.

[0015] Furthermore, the sheet-shaped copper powder is arranged at an angle α to the surface of the copper grid line, where 0°≤α≤45°.

[0016] Furthermore, the area of ​​the sheet-shaped copper powder applied to the surface of the copper grid line is 30%-70% of the surface area of ​​the copper grid line.

[0017] This application also provides a solar cell comprising the aforementioned copper grid lines.

[0018] Furthermore, the surface of the solar cell has a textured surface, and the copper grid lines are located on the upper part of the textured surface of the solar cell.

[0019] Furthermore, the height of the outer portion of the copper grid line is 0.05-2.5 micrometers.

[0020] The copper grid line described in this application has a certain width of peripheral portion on both sides of the main grid line portion. The median particle size of the copper powder in the peripheral portion is smaller than that in the main grid line portion. This allows for the formation of a dense structure in the peripheral portion, increasing the contact area between the copper grid line and the battery surface, improving the adhesion of the copper grid line, and preventing water and oxygen from penetrating from the interface between the copper grid line and the bottom battery and oxidizing the copper powder in the main grid line portion. This reduces the bulk resistivity of the grid line and the contact resistance between the grid line and the battery. Simultaneously, the width of the peripheral portion on either side does not exceed 15%-50% of the width of the main grid line portion, ensuring that the copper grid line has low bulk resistivity and contact resistance, while also ensuring a low light shading rate.

[0021] The resistivity of the copper grid wire described in this application is less than 25 μΩ·cm, and the contact resistivity is no more than 1 mΩ·cm. 2 Its efficiency is comparable to that of silver paste. Attached Figure Description

[0022] Figure 1 This is a schematic diagram of the copper grid lines in this application.

[0023] Figure 2 This is a schematic diagram of the outer portion of the copper grid line in this application.

[0024] Figure 3 This is a schematic diagram of the copper grid surface of this application. Detailed Implementation

[0025] The present application will now be described in detail with reference to the described embodiments. Although specific embodiments of the present application are shown, it should be understood that the present application can be implemented in various forms and should not be limited to the embodiments set forth herein. Rather, these embodiments are provided so that this application will be thorough and complete, and will fully convey the scope of the present application to those skilled in the art.

[0026] It should be noted that certain terms are used in the specification and claims to refer to specific components. Those skilled in the art will understand that different terms may be used to refer to the same component. This specification and claims do not distinguish components based on differences in terminology, but rather on differences in function. The terms "comprising" or "including" used throughout the specification and claims are open-ended and should be interpreted as "comprising but not limited to." The following descriptions in the specification are preferred embodiments for carrying out this application; however, these descriptions are for the purpose of understanding the general principles of the specification and are not intended to limit the scope of this application. The scope of protection of this application shall be determined by the appended claims.

[0027] This application provides a copper grid line, comprising a grid line body portion and a grid line periphery portion, wherein the grid line periphery portion is located on both sides of the grid line body portion, and the width of the grid line periphery portion on either side does not exceed 15%-50% of the width of the grid line body portion; the median value of the copper powder particle size of the grid line periphery portion is smaller than the median value of the copper powder particle size of the grid line body portion.

[0028] In this application, no restrictions are placed on the method for measuring the width of the main body of the gate line. The art can make conventional choices based on actual needs. For example, the width of the main body of the gate line can be obtained by SEM measurement. For example, the width of the bottom of the copper gate line in a certain area within the field of view can be measured by SEM, and the average value can be calculated by continuously measuring 10 areas to obtain the width of the main body of the gate line.

[0029] In this application, the height of the copper powder coverage in the main body of the gate line is significantly different from that in the peripheral area of ​​the gate line, and the particle size is significantly different from that in the peripheral area of ​​the gate line. The area with a high copper powder coverage and a relatively large copper powder particle size is the main body of the gate line, while the portion extending to both sides from the main body of the gate line is the peripheral area of ​​the gate line.

[0030] In this application, no restrictions are placed on the measurement of the width of the outer portion of the gate line. Those skilled in the art can determine it using conventional methods, such as SEM measurement. For example, since the height of copper powder coverage in the areas containing the main body and the outer portion of the gate line differs significantly, and the particle size of the copper powder in the two areas also differs significantly, the boundary between the main body and the outer portion of the copper gate line can be found using SEM. This boundary is used as the starting line for the outer portion of the gate line, extending outwards to both sides. The center of the area where the projected area of ​​copper powder per unit square centimeter accounts for 30%-40% is taken as the measurement endpoint. The vertical distance between the starting point and the endpoint relative to the line containing the gate line is defined as the width of the outer portion of the gate line. Ten measurement positions are randomly selected for a test sample of a gate line. For example, the width of the outer portion of the gate line on any one side does not exceed 15%, 20%, 25%, 30%, 35%, 40%, 45%, or 50% of the width of the main body of the gate line.

[0031] Figure 1 This is a copper grid line in a specific embodiment of the present application, wherein 1 is the main body of the grid line, 2 is the outer periphery of the grid line, and 3 is the part of the grid line that is not diffused. The width of the outer periphery of the grid line 2 on any side does not exceed 15%-50% of the width of the main body of the grid line 1.

[0032] Figure 2 This is an electron microscope image of the outer portion of the copper grid. Figure 2 The block diagram in the image illustrates the diffusion of copper powder from the outer portion of the copper grid lines into the pyramid-shaped textured surface. Figure 2 It can be seen that the copper powder in the copper paste diffuses into the pyramid-shaped textured surface to form a dense structure.

[0033] In some embodiments, the width of the main body portion of the copper grid line is 30-120 micrometers. In some embodiments, the width of the outer portion of the copper grid line is 10-60 micrometers. For example, the width of the main body portion of the copper grid line can be 30 micrometers, 35 micrometers, 40 micrometers, 45 micrometers, 50 micrometers, 55 micrometers, 60 micrometers, 65 micrometers, 70 micrometers, 75 micrometers, 80 micrometers, 85 micrometers, 90 micrometers, 95 micrometers, 100 micrometers, 105 micrometers, 110 micrometers, 115 micrometers, 120 micrometers, etc.

[0034] For example, the width of the outer portion of the copper grid line can be 10 micrometers, 15 micrometers, 20 micrometers, 25 micrometers, 30 micrometers, 35 micrometers, 40 micrometers, 45 micrometers, 50 micrometers, 55 micrometers, 60 micrometers, etc.

[0035] In some embodiments, the height of the main body of the copper grid line is 10-25 micrometers. In some embodiments, the height of the outer portion of the copper grid line is 0.05-2.5 micrometers.

[0036] In this application, the height of the main body of the copper grid line refers to the vertical height at the center point of the bottom edge of the copper grid line cross-section. This height is measured using SEM (Scanning Electron Microscopy). The vertical height at the center point of the bottom edge of the grid line cross-section is measured at any 20 locations on the test sample, and the average value is calculated. This average value is the height of the main body of the copper grid line. Those skilled in the art will understand that the above method is merely exemplary, and they can appropriately reduce or increase the number of measurement locations on the selected copper grid line based on actual circumstances.

[0037] This application does not impose any restrictions on the measurement of the height of the outer portion of the gate line. Those skilled in the art can determine this using conventional methods, such as SEM (Scanning Electron Microscopy). For example, after determining the test area of ​​the outer portion of the gate line according to the aforementioned method, the thickness of the outer portion of the gate line at any 10 locations within the test area can be measured, i.e., the height of the outer portion of the gate line. Those skilled in the art will also understand that the above method is merely exemplary, and they can appropriately reduce or increase the number of measurement locations for the selected copper gate line based on actual circumstances.

[0038] For example, the height of the main body of the copper grid line can be 10 micrometers, 11 micrometers, 12 micrometers, 13 micrometers, 14 micrometers, 15 micrometers, 16 micrometers, 17 micrometers, 18 micrometers, 19 micrometers, 20 micrometers, 21 micrometers, 22 micrometers, 23 micrometers, 24 micrometers, 25 micrometers, etc.

[0039] For example, the height of the outer portion of the copper grid line can be 0.05 micrometers, 0.1 micrometers, 0.3 micrometers, 0.5 micrometers, 0.7 micrometers, 0.9 micrometers, 1 micrometer, 1.2 micrometers, 1.4 micrometers, 1.6 micrometers, 1.8 micrometers, 2.0 micrometers, 2.2 micrometers, or 2.5 micrometers.

[0040] This application sets the height of the main body of the copper grid line, the width of the outer perimeter, and the width of the main body within the above three value ranges. The resulting copper grid line can not only have a firm contact with the solar cell and reduce resistivity and improve current collection efficiency, but also have a small shading rate to light and reduce the cost of using the copper grid line.

[0041] In some embodiments, the copper grid line comprises micron-sized flake copper powder and nano-sized spherical copper powder, wherein the median particle size of the spherical copper powder is 100-700 nm, the median diameter of the flake copper powder is 2-8 μm, and the median thickness of the flake copper powder is 100-500 nm.

[0042] For example, the median particle size of the spherical copper powder can be 100nm, 150nm, 200nm, 250nm, 300nm, 350nm, 400nm, 450nm, 500nm, 550nm, 600nm, 650nm, 700nm, etc.

[0043] The median diameter of the flake-shaped copper powder can be 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, etc.

[0044] The median thickness of the sheet-shaped copper powder can be 100nm, 150nm, 200nm, 250nm, 300nm, 350nm, 400nm, 450nm, 500nm, etc.

[0045] In this paper, the median refers to the particle size at which the cumulative volumetric particle size distribution percentage of a sample reaches 50%. Physically, it means that 50% of the particles are larger than the median, and 50% are smaller.

[0046] In this application, no restrictions are placed on the method for determining the median particle size of copper powder. Conventional methods in the art can be used, such as SEM (Scanning Electron Microscopy). For example, photographs are taken of 10 different regions of the test sample. Then, for each photograph, the dimensions of 10 flake-shaped copper powder particles observed are measured along the horizontal plane, and the median value is calculated; this is the median diameter. Similarly, the dimensions are measured along the vertical plane, and the median value is calculated; this is the median thickness. For each photograph, the diameter of 10 spherical copper powder particles observed is measured, and the median value is calculated; this is the median particle size of the spherical copper powder. This method is used for both flake-shaped and spherical copper powders described below.

[0047] In some embodiments, the micron-sized flake copper powder comprises 40-70% by mass percentage in the copper powder, and the nano-sized spherical copper powder comprises 30-60%.

[0048] For example, the micron-sized flake copper powder can be 40%, 45%, 50%, 55%, 60%, 65%, 70%, etc., based on its mass percentage in the copper powder; and the nano-sized spherical copper powder can be 30%, 35%, 40%, 45%, 50%, 55%, 60%, etc.

[0049] In this application, the flake copper powder has a larger particle size, resulting in a larger contact area and better conductivity, while the spherical copper powder has a smaller particle size, allowing it to better fill the gaps in the pyramidal textured surface and reduce contact resistance. Therefore, by controlling the size and / or mass ratio of the flake and spherical copper powders, both the bulk resistivity and contact resistance of the gate line can be kept within a low range.

[0050] In some embodiments, the copper grid lines comprise nanoscale spherical copper powder and micron-scale flake-shaped copper powder, with the outer portion of the grid lines comprising only nanoscale spherical copper powder. In some embodiments, the copper grid lines are prepared by screen printing.

[0051] This application does not impose any limitations on the screen printing method. Those skilled in the art can use conventional methods in the art to screen print copper paste. For example, the width of the outer portion of the grid lines and the width and height of the main portion of the grid lines can be achieved by controlling the printing pressure, squeegee hardness, squeegee angle, and other processes of screen printing. Those skilled in the art can obtain these process conditions through conventional optimization as needed.

[0052] In some embodiments, the copper grid line comprises nanoscale spherical copper powder and micron-scale flake copper powder, the surface of the flake copper powder being adhered to the surface of the copper grid line in a substantially horizontal state. Combined with Figure 3 It can be seen that the sheet copper powder is applied to the surface of the copper grid line in a basically horizontal state. The surface of the copper grid line here refers to the tangent of the surface of the copper grid line where the sheet copper powder intersects with the electrode.

[0053] In the copper grid wire of this application, sheet-shaped copper powder with better oxidation resistance is applied to the surface of the copper grid wire in a near-horizontal or horizontal state to improve the overall oxidation resistance of the copper grid wire when placed in the air and reduce the resistivity of the copper grid wire.

[0054] Furthermore, the sheet-shaped copper powder is arranged at an angle α to the surface of the copper grid line, where 0°≤α≤45°. Figure 3 This is a schematic diagram of the copper grid surface, combined with... Figure 3 It can be seen that α is the tilt angle of the sheet-like copper powder on the surface of the copper grid line relative to the surface of the copper grid line, and α here is 32.7°.

[0055] In this application, the α angle is measured using SEM (Scanning Electron Microscopy). A sheet of copper powder is selected within the field of view, and the midpoint of the intersection line between the horizontal plane of the sheet of copper powder and the surface of the copper grid line is chosen. A tangent line is drawn to the surface of the copper grid line using this midpoint, and the angle between the horizontal plane of the sheet of copper powder and this tangent line is calculated to obtain an α angle. The same method is used to measure the α angle of more than 10 sheet of copper powder in different regions of the test sample, and the average value of all measured α angles is calculated. Those skilled in the art will also understand that the above method is merely exemplary, and those skilled in the art can appropriately reduce or increase the photographed area or number of test samples based on actual circumstances.

[0056] In some implementations, 0°≤α≤40°.

[0057] In some implementations, 0°≤α≤35°.

[0058] In some implementations, 0°≤α≤30°.

[0059] In some implementations, 0°≤α≤25°.

[0060] In some implementations, 5°≤α≤40°.

[0061] In some implementations, 5° ≤ α ≤ 35°.

[0062] In some implementations, 5° ≤ α ≤ 30°.

[0063] In some implementations, 5°≤α≤25°.

[0064] Specifically, α can be 45°, 42°, 40°, 38°, 35°, 32°, 30°, 28°, 25°, 22°, 20°, 18°, 15°, 12°, 10°, 8°, 5°, etc.

[0065] Furthermore, the area of ​​the sheet-shaped copper powder applied to the surface of the copper grid line is 30%-70% of the surface area of ​​the copper grid line.

[0066] In the copper grid line of this application, the shape difference between sheet powder and ball powder can be further utilized to control the surface area ratio of sheet copper powder on the surface of the copper grid line, thereby improving the firmness of the sheet copper powder on the surface and ensuring that the copper grid line has a high copper powder filling rate, and further reducing the resistivity of the copper grid line.

[0067] In this paper, the projected area of ​​the sheet-like copper powder on the surface of the copper grid line is obtained by SEM (Scanning Electron Microscopy). The surface area of ​​the copper grid line is obtained by 3D microscopy. The shape and size of the copper grid line are measured by 3D microscopy, and then its surface area is calculated. The cross-section of the copper grid line is generally trapezoidal or trapezoidal-like, and this cross-section is perpendicular to the extension direction of the copper grid line. The upper base a, lower base b, and height h of the trapezoid, as well as the length l of the copper grid line, are measured, and the surface area of ​​the copper grid line is calculated by the following formula:

[0068] Specifically, the area of ​​the sheet-like copper powder located on the surface of the copper grid line, as a percentage of the surface area of ​​the copper grid line, can be 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, etc.

[0069] In this application, no restrictions are placed on the copper paste material, as long as the copper paste material is screen printed to obtain the aforementioned copper grid lines.

[0070] For example, the copper paste comprises micro / nano copper powder, polymer resin, solvent, curing agent, and dispersant. In some embodiments, the micro / nano copper powder comprises micron-sized flake-shaped copper powder and nano-sized spherical copper powder.

[0071] The median value of the micron-sized flake copper powder is 2-8 μm, and the median value of the nano-sized spherical copper powder is 100-700 nm.

[0072] In this application, to remove oxygen-containing substances from the surface of the original copper powder and improve its antioxidant capacity, the copper powder is obtained by surface passivation agent treatment. This application does not impose any restrictions on the surface treatment method for the powder; those skilled in the art can use conventional methods to surface treat the copper powder. For example, the copper powder can be treated as follows: after acid washing, the copper powder is redispersed in alcohol, a passivation agent is added and stirred, followed by separation and drying to obtain passivation agent-pretreated copper powder. Further, the passivation agent is selected from one or more of the following: saturated / unsaturated fatty acids containing 8-18 carbons, silane coupling agents, PVP, and thiols.

[0073] In some embodiments, the micron-sized flake copper powder comprises 40-70% by mass percentage in the copper powder, and the nano-sized spherical copper powder comprises 30-60%.

[0074] For example, the micron-sized flake copper powder can be 40%, 45%, 50%, 55%, 60%, 65%, 70%, etc., based on its mass percentage in the copper powder;

[0075] The nanoscale spherical copper powder can be 30%, 35%, 40%, 45%, 50%, 55%, 60%, etc.

[0076] In some embodiments, the copper powder comprises 87-93% by mass percentage in the copper paste, the dispersant comprises 1-5%, the polymer resin comprises 2-4%, the solvent comprises 3-6%, and the curing agent comprises 0.2-0.4%.

[0077] For example, the copper powder can be 87%, 88%, 89%, 90%, 91%, 92%, 93%, etc., based on its mass percentage in the copper paste;

[0078] The dispersant can be 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, etc.;

[0079] The polymer resin can be 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.6%, 2.9%, 3.0%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4%, etc.

[0080] The solvent can be 3%, 3.5%, 4.0%, 4.5%, 5.0%, 5.5%, 6%, etc.;

[0081] The curing agent can be 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, etc.;

[0082] This application does not impose any restrictions on the types of polymer resins, solvents, and curing agents. Those skilled in the art can make conventional selections based on their needs. For example, the polymer resin can be one or a combination of two of epoxy resins, polyurethane resins, polyester resins, and phenolic resins.

[0083] The solvent may be one or two of ethylene glycol butyl ether, ethylene glycol dimethyl ether, dipropylene glycol butyl ether, isophorone, and diethylene glycol butyl ether.

[0084] The curing agent can be one of latent imidazole, boron trifluoride ethylamine, or disubstituted urea.

[0085] In some embodiments, the dispersant may be an ester and / or an alcohol, wherein the ester dispersant is selected from one or more of divalent esters (DBE), diethylene glycol butyl ether acetate, ethylene glycol butyl ether acetate, triethyl phosphate, and triethyl phosphite; and the alcohol dispersant is selected from one or more of ethylene glycol, 1,2-propylene glycol, glycerol, pentaerythritol, polyethylene glycol 400, polyethylene glycol 600, polypropylene glycol 400, and polypropylene glycol 600, preferably a mixture of esters and alcohols. In some embodiments, the mass ratio of the ester compound to the alcohol compound is 1:1-4.

[0086] For example, the mass ratio of the ester compound to the alcohol compound (m 酯类化合物 :m 醇类化合物 The ratios can be 1:1, 1:2, 1:3, 1:4, etc.

[0087] This application utilizes a mixture of esters and alcohols as a dispersant to increase the dispersibility of copper powder. This facilitates the dispersion of smaller-sized nano-copper powder to the periphery of the grid lines, located at the base of the pyramid on the textured surface of the solar cell. This increases the contact area between the copper grid lines and the ITO or TCO on the cell surface, reducing contact resistance. Therefore, the diffusion width of the periphery of the grid lines can be controlled by adjusting the type of dispersant.

[0088] This application provides a solar cell comprising the copper grid lines described in any of the preceding embodiments. In some embodiments, the solar cell has a textured surface structure with light-trapping properties to increase solar radiation collection efficiency. The textured surface structure is a surface with a regular or irregular shape, used to scatter incident light and reduce the amount of light reflected back from the surface of the solar cell; specifically, it can be a pyramidal structure.

[0089] The copper grid lines are located at the top of the pyramid structure of the solar cell.

[0090] In this application, the pyramid is a TCO layer. The pyramid structure is an inverted triangle structure, which can only be densely filled if the powder particle size is small enough. The main part of the grid line is composed of flake copper powder and spherical copper powder. The flake copper powder and spherical copper powder are closely packed together in terms of size and shape. During printing, only the fine-particle-size nano-spherical copper powder diffuses to the outer part of the grid line and tightly fills the bottom of the pyramid structure, while most of the flake copper powder is blocked outside the pyramid structure, thereby obtaining good contact resistance.

[0091] Furthermore, on the surface of the solar cell, the height of the outer portion of the copper grid lines is 0.05-2.5 micrometers. If the height of the outer portion of the copper grid lines is too large, it will increase the bulk resistance of the grid lines; if the height is too small, it will not effectively increase the adhesion between the copper grid lines and the solar cell, nor will it achieve good contact resistance. In this paper, when the copper grid lines contact the solar cell surface using a pyramid-shaped textured surface structure, the smaller-sized nano-spherical copper powder will fill the bottom of the pyramid. The height of the outer portion of the copper grid lines is measured from the lowest point where the copper powder fills the bottom of the pyramid.

[0092] In some embodiments, the solar cell is selected from BC cells, HJT cells, and perovskite / crystalline silicon tandem cells.

[0093] In this application, perovskite / crystalline silicon tandem solar cell refers to a crystalline silicon-perovskite tandem solar cell, where the crystalline silicon cell can be an HJT cell, etc. It employs a composite material as the light-absorbing layer, primarily composed of perovskite and silicon materials. This material features high absorption rate and high conversion efficiency, enabling it to convert sunlight into electrical energy.

[0094] BC cells refer to back-contact cells, where the PN junction and metal contacts are located on the back of the solar cell. The front of the cell uses a double-layer SiNx / SiOx anti-reflection passivation film. Without metal electrodes to block the light, it maximizes the use of incident light, reduces optical losses, brings more effective power generation area, has high conversion efficiency, and is more aesthetically pleasing.

[0095] HJT cells are a new type of solar cell technology, also known as silicon heterojunction solar cells.

[0096] Example

[0097] This application provides a general and / or specific description of the materials and test methods used in the experiments. In the following examples, unless otherwise specified, % represents wt%, i.e., weight percentage. Reagents or instruments used, unless otherwise specified, are all commercially available conventional reagent products.

[0098] Example 1

[0099] (1) Add 2g of epoxy resin and 1g of phenolic resin to 5g of DBE solvent, stir and mix at room temperature, and then filter with a 500-mesh sieve to remove impurities to obtain a polymer resin solution.

[0100] (2) Add 0.5g of dispersant polyethylene glycol 400 and 0.5g of dispersant triethyl phosphate to the above polymer resin solution and stir thoroughly to disperse evenly. Then add 0.3g of latent imidazole as curing agent to the above solution and disperse thoroughly. Next, add 45g of nano-spherical copper powder (median particle size of 200nm) and 45g of micron-sized flake copper powder (median diameter of 2μm and thickness of 100nm) to a planetary mixer for premixing to obtain a premix.

[0101] (3) The obtained premixed material is subjected to high-speed shearing and grinding in a three-roll mill to obtain low-temperature conductive copper paste. The copper paste is then passed through a 400-mesh sieve to remove impurities and large particles, and then vacuum degassing is performed to obtain copper paste material.

[0102] The copper paste obtained in Example 1 was screen-printed onto a solar cell to prepare grid lines. The obtained grid lines were then photographed using SEM, as shown below. Figure 1 , Figure 2 and Figure 3 As shown, where Figure 1 In the diagram, 1 represents the main body of the gate line, 2 represents the outer periphery of the gate line, and 3 represents the portion of the gate line that has not diffused. Looking at the cross-section of the gate line, the outer periphery contains spherical copper powder with a smaller particle size than the main body of the gate line, and the median particle size is less than 200 nm. Figure 2 It can be seen that the copper powder in the copper paste is distributed at the bottom of the cell surface, forming a dense structure. Figure 3 It can be seen that the angle α between the sheet-shaped copper powder and the surface of the copper grid line is 32.7°, and the sheet-shaped copper powder is observed to be adhered to the grid line surface in a basically horizontal state. The contact resistivity between the grid line and the cell was tested using a TLM contact resistance tester commonly used in the art. The contact resistivity eliminates the influence of grid line width, spacing, and ITO sheet resistance. The results are shown in Table 1, which also shows the width and height of the main body of the grid line and the width of the outer portion of one side of the grid line.

[0103] Example 2

[0104] The difference between Example 2 and Example 1 is that: 3g of polyethylene glycol 400 and 1g of dispersant diethylene glycol butyl ether acetate were used to prepare copper paste, and the grid lines were prepared in the same way as in Example 1. The cell rate and contact resistivity, the width and height of the main body of the grid lines and the width of the outer portion of the grid lines on one side were measured.

[0105] Example 3

[0106] The difference between Example 3 and Example 1 is that the median diameter of the micron-sized flake copper powder is 10 μm, and the grid lines are prepared in the same way as in Example 1. The cell rate and contact resistivity, the width and height of the main body of the grid lines, and the width of the outer portion of the grid lines on one side are measured.

[0107] Example 4

[0108] The difference between Example 4 and Example 1 is that the median particle size of the nano-spherical copper powder is 900 nm, and the grid lines are prepared in the same way as in Example 1. The cell rate and contact resistivity, the width and height of the main body of the grid lines, and the width of the outer part of the grid lines on one side are measured.

[0109] Example 5

[0110] The difference between Example 5 and Example 1 is that: the amount of nano-spherical copper powder used is 18g, and the amount of micron-sized flake copper powder used is 72g to prepare copper paste. The grid lines are prepared in the same way as in Example 1, and the cell rate and contact resistivity, the width and height of the main body of the grid lines and the width of the outer part of the grid lines on one side are measured.

[0111] Example 6

[0112] The difference between Example 6 and Example 1 is that the amount of nano-spherical copper powder used is 27g and the amount of micron-sized flake copper powder used is 63g to prepare copper paste. The grid lines are prepared in the same way as in Example 1, and the cell rate and contact resistivity, the width and height of the main body of the grid lines and the width of the outer part of the grid lines on one side are measured.

[0113] Example 7

[0114] The difference between Example 7 and Example 1 is that the median diameter of the micron-sized flake copper powder is 8 μm, and the grid lines are prepared in the same way as in Example 1. The cell rate and contact resistivity, the width and height of the main body of the grid lines, and the width of the outer portion of the grid lines on one side are measured.

[0115] Example 8

[0116] The difference between Example 8 and Example 1 is that the median particle size of the nano-spherical copper powder is 700 nm, and the grid lines are prepared in the same way as in Example 1. The cell rate and contact resistivity, the width and height of the main body of the grid lines and the width of the outer portion of the grid lines on one side are measured.

[0117] Comparative Example 1

[0118] The difference between Comparative Example 1 and Example 1 is that Comparative Example 1 uses only polyethylene glycol 400 to prepare copper paste and prepares grid lines in the same way as Example 1, and measures cell rate and contact resistivity, grid line body width and height, and the width of one side of the grid line periphery.

[0119] Comparative Example 2

[0120] The difference between Comparative Example 2 and Example 1 is that Comparative Example 2 uses only spherical copper powder to prepare copper paste, and prepares grid lines in the same way as Example 1, and measures cell rate and contact resistivity, width and height of the main body of the grid line, and width of the outer portion of the grid line on one side.

[0121] Table 1

[0122]

[0123] As can be seen from the table above, when the width of the outer portion of the grid line on any side does not exceed 15%-50% of the width of the main body of the grid line, the resistivity and contact resistivity of the copper grid line are both low.

[0124] The above description is merely a preferred embodiment of this application and is not intended to limit the application in any other way. Any person skilled in the art may make changes or modifications to the disclosed technical content to create equivalent embodiments. However, any simple modifications, equivalent changes, and modifications made to the above embodiments based on the technical essence of this application without departing from the scope of the technical solution of this application shall still fall within the protection scope of this application.

Claims

1. A copper grid wire, comprising a grid wire body portion and a grid wire periphery portion, wherein the grid wire periphery portion is located on both sides of the grid wire body portion, wherein the width of the grid wire periphery portion on either side is 15%-50% of the width of the grid wire body portion; the median value of the copper powder particle size of the grid wire periphery portion is smaller than the median value of the copper powder particle size of the grid wire body portion; The width of the main body of the copper grid line is 30-120 micrometers; The height of the outer portion of the copper grid line is 0.05-2.5 micrometers; The height of the main body of the copper grid line is 10-25 micrometers.

2. The copper grid line according to claim 1, wherein, The width of the outer portion of the copper grid line is 10-60 micrometers.

3. The copper grid line according to claim 1, wherein, The copper grid line comprises nanoscale spherical copper powder and micron-scale flake copper powder. The median particle size of the spherical copper powder is 100-700 nm, the median diameter of the flake copper powder is 2-8 μm, and the median thickness of the flake copper powder is 100-500 nm.

4. The copper grid line according to claim 3, wherein, The micron-sized flake copper powder accounts for 40-70% of the total copper powder by mass percentage, and the nano-sized spherical copper powder accounts for 30-60%.

5. The copper grid line according to any one of claims 1-4, wherein the copper grid line comprises nanoscale spherical copper powder and micron-scale flake copper powder, and the outer portion of the grid line comprises only nanoscale spherical copper powder.

6. The copper grid wire according to any one of claims 1-4, wherein, The copper grid lines are prepared by screen printing.

7. The copper grid wire according to any one of claims 1-4, wherein, The copper grid line comprises nanoscale spherical copper powder and micron-scale flake copper powder, with the surface of the flake copper powder adhered to the surface of the copper grid line in a substantially horizontal state.

8. The copper grid line according to claim 7, wherein, The sheet-shaped copper powder is arranged at an angle α to the surface of the copper grid line, where 0°≤α≤45°.

9. The copper grid line according to claim 7, wherein, The area of ​​the sheet-shaped copper powder applied to the surface of the copper grid line is 30%-70% of the surface area of ​​the copper grid line.

10. A solar cell comprising copper grid lines according to any one of claims 1-9.

11. The solar cell according to claim 10, wherein, The surface of the solar cell has a textured surface, and the copper grid lines are located on the upper part of the textured surface of the solar cell.

Citation Information

Patent Citations

  • Photovoltaic cell, preparation method thereof and photovoltaic module

    CN118299437A